Understanding and improving endometrial receptivity. Issue 3 (June 2015) - Miravet-Valenciano, Jose A.; Rincon-Bertolin, Alejandro; Vilella, Felipe; Simon, Carlos
Abstract : Purpose of the review: For a successful pregnancy, the synchronic coordination between the embryonic development and the endometrial status is crucial. The endometrium is a hormonally regulated organ that is nonadhesive to embryos throughout most of the menstrual cycle in humans. Endometrial receptivity refers to a hormone-limited period in which the endometrial tissue acquires a functional and transient ovarian steroid-dependent status allowing blastocyst implantation and therefore pregnancy initiation. Recent findings: Our group has developed the endometrial receptivity array (ERA), a customized array based on the expression of 238 genes coupled to a computational predictor capable of diagnosing a functionally receptive endometrium regardless of its histological appearance. Clinical results obtained in our laboratory demonstrate the diagnostic and therapeutic efficiency of the ERA test in patients with implantation failure, allowing the personalization of the optimal day for embryo transfer. Summary: To keep improving the global knowledge of endometrial receptivity stage, new high-throughput techniques like RNA-seq or genome-wide association studies will be crucial in the near future. Also the identification of new biomarkers of endometrial receptivity that could be assessed by noninvasive methods has become a challenging goal to help diagnose the endometrial status to increase implantation rates and pregnancy outcomes in patients undergoing assisted reproductive treatments.